“Ideal employees” and “good wives and mothers”: Influence mechanism of bi-directional work–family conflict on job satisfaction of female university teachers in China - Su, Qiaolan; Jiang, Man (Frontiers in Psychology, 2023)
Work and family are two important areas in people's life, and the relationship between them will have an important impact on the attitudes and behaviors of employees in an organization. In the context of Chinese culture, the organization hopes to have an ideal employee, and the family hopes to have a good wife and mother. Based on the resource conservation theory, this paper examines the relationship between bi-directional work-family conflict and job burnout, perceived organizational support and job satisfaction by using latent variable path analysis method with 527 Chinese female university teachers as subjects. The results showed that: (1) Work-family conflict, family-work conflict and job burnout could negatively predict job satisfaction, while perceived organizational support could positively predict job satisfaction; (2) Job burnout played a partial mediating role in the process of work-family conflict and family-work conflict affecting job satisfaction, and the effect values were -0.220 and -0.168; (3) Perceived organizational support played a moderating role in the first half of the mediating effect of "work-family conflict→job burnout→job satisfaction" and "family-work conflict→job burnout→job satisfaction", and the moderating mediating index was 0. 015 and 0. 010. The study contributes to a better understanding of the relationships among bi-directional work-family conflict, job burnout, perceived organizational support, and job satisfaction among female university teachers. Our findings highlight potential avenues for interventions by university administrators in the context of Chinese culture aimed at balancing work and family and improving job satisfaction among female university teachers.